Aspectos formais da trilha musical de Yasunori Mitsuda para o game Chrono Cross e sua interação com o enredo - Roveran, Luiz Fernando Valente [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This work has the aim of evince compositional tools used in the development of musical scores for role-playing videogames through the analysis of Yasunori Mitsuda’s music for Chrono Cross (1999). This research is divided in two main parts: the first traces a historic path of the RPG genre on videogame consoles, since its birth as a tabletop game in the decade of 1970 until its consolidation on 3D game machines released in the 1990’s. The focus of this historical study concentrates on the aesthetics of this kind of game and on the multiple relations it settles with sound throughout the years. The second part is an analytical work on an assortment of pieces by Mitsuda for the aforementioned game, bringing up the most interesting aspects of the connections established between these compositions and the whole game.

Este trabalho teve por finalidade evidenciar recursos composicionais utilizados no desenvolvimento de trilhas musicais de RPGs (Role-playing games) eletrônicos através da análise da obra de Yasunori Mitsuda para Chrono Cross (1999). Para tanto, dividiu-se esta pesquisa em duas grandes partes: a primeira traça um caminho histórico do gênero RPG nos consoles de videogame, desde o seu surgimento como jogo de mesa na década de 1970 até sua consolidação nos aparelhos de games tridimensionais lançados na década de 1990. O enfoque desta historicidade se concentra na estética deste tipo de jogo e nas múltiplas relações que o som erige com ele ao longo dos anos. A segunda parte é um trabalho analítico sobre uma seleção de peças de Mitsuda para o game supracitado, levantando os aspectos mais interessantes das conexões estabelecidas entre estas músicas e a obra como um todo.
Keywords: Mitsuda, Yasunori 1972-; Música; Jogos eletronicos; Jogos de fantasia; Eletronic Games